Smokey comes of age: unmanned aerial systems for fire management. Issue 6 (1st August 2016) - Twidwell, Dirac; Allen, Craig R; Detweiler, Carrick; Higgins, James; Laney, Christian; Elbaum, Sebastian
Abstract : During the past century, fire management has focused on techniques both to protect human communities from catastrophic wildfire and to maintain fire‐dependent ecological systems. However, despite a large and increasing allocation of resources and personnel to achieve these goals, fire management objectives at regional to global scales are not being met. Current fire management techniques are clearly inadequate for the challenges faced by fire managers, and technological innovations are needed. Advances in unmanned aerial systems (UAS) technology provide opportunities for innovation in fire management and science. In many countries, fire management organizations are beginning to explore the potential of UAS for monitoring fires. We have taken the next step and developed a prototype that can precisely ignite fires as part of wildfire suppression tactics or prescribed fires (fire intentionally ignited within predetermined conditions to reduce hazardous fuels, improve habitat, or mitigate for large wildfires). We discuss the potential for these technologies to benefit fire management activities, while acknowledging the sizeable sociopolitical barriers that prevent their immediate broad application.